Application of CUSA Excel ultrasonic aspiration system in resection of skull base meningiomas - Tang, Hailiang; Zhang, Haishi; Xie, Qing; Gong, Ye; Zheng, Mingzhe; Wang, Daijun; Zhu, Hongda; Chen, Xiancheng; Zhou, Liangfu (Chinese Journal of Cancer Research; Vol 26, No 6 (December 30, 2014): Chinese Journal of Cancer Research, 2014)
Background: Here, we introduced our short experience on the application of a new CUSA Excel ultrasonic aspiration system, which was provided by Integra Lifesciences corporation, in skull base meningiomas resection. Methods: Ten patients with anterior, middle skull base and sphenoid ridge meningioma were operated using the CUSA Excel ultrasonic aspiration system at the Neurosurgery Department of Shanghai Huashan Hospital from August 2014 to October 2014. There were six male and four female patients, aged from 38 to 61 years old (the mean age was 48.5 years old). Five cases with tumor located at anterior skull base, three cases with tumor on middle skull base, and two cases with tumor on sphenoid ridge. Results: All the patents received total resection of meningiomas with the help of this new tool, and the critical brain vessels and nerves were preserved during operations. All the patients recovered well after operation. Conclusions: This new CUSA Excel ultrasonic aspiration system has the advantage of preserving vital brain arteries and cranial nerves during skull base meningioma resection, which is very important for skull base tumor operations. This key step would ensure a well prognosis for patients. We hope the neurosurgeons would benefit from this kind of technique.